Specific processes for admission of athletes to undergraduate programs at Brazilian federal universities - Silva, Junior Vagner Pereira da; Quinaud, Ricardo Teixeira; Grubertt, Guilherme Alves; Costa, Felipe Rodrigues; Figueiredo, António José (Frontiers in Education, 2025)
IntroductionUniversity education for athletes is an important part of preparing them for their career transition. Therefore, specific selection processes for athletes can contribute to this process.MethodsThis is a qualitative-quantitative, cross-sectional, exploratory and documentary study, with content analysis.Results68 Brazilian federal universities took part in the study. After completing the first stage of the research, it was possible to identify that only two higher education institutions (the Federal University of Mato Grosso do Sul and the Federal University of Santa Maria) had specific public notices in 2023 for the admission of athletes to higher education. These institutions, therefore, constitute the object of analysis of this investigation. The Federal University of Mato Grosso do Sul made 103 places available to athletes who won first, second or third place in regional, national or international competitions between 2021 and 2023, with no age or score limits, covering 46 sports, 65.21% of which are part of the Brazilian University Games and 63.04% of which are part of the Olympic Games. All paralympic sports are covered. Of the places on offer, 29.12% were sought after and 53.33% of applicants were admitted to higher education. At the Federal University of Santa Maria has allocated 66 places for junior athletes (16 to 23 years old) in futsal, handball, volleyball and athletics. For former athletes, there was no restriction on the number of sports. For the Federal University of Mato Grosso do Sul, the ratio of enrolled athletes to places was 0.29, and the ratio of admitted athletes to places was 0.15. The ratio in the Federal University of Santa Maria enrolled athletes to places was 0.59, and the ratio of admitted athletes to places was 0.12. The conclusion is that the programs promoted are important initiatives but have limitations that need to be remedied.